Assessing the Effect of Electronic Pseudopotentials and Relativistic Treatments on the Structural and Electrical Properties of GaN: A DFT Study - Das, D. K.; Patnaik, P.; Nayak, S.K.; Barala, M. (Physics and Chemistry of Solid State, 2023)
Applying the principle of Density functional theory, we can calculate various parameters like lattice constant, band gap, band plot, dielectric function plot, refractive index plot, conductivity plot, density of state plot, loss function etc. of GaN. In this work, we use different electronic pseudopotentials with different relativistic treatment studied using Local density approximation functional (LDA-CAPZ) within DFT for GaN. We used to calculate the energy values, lattice parameters change after geometry optimisation and plot the band energies. Electronic structure calculations results are compares taking different electronic pseudopotentials of different cut-off energy having different relativistic approaches. The Density of state plot and partial density of states plot help to studied more about the electronic as well as magnetic characteristics of the GaN sample. Here, we also compare the advantages and disadvantages of different pseudopotentials with different relativistic approaches of the sample. Energy level distribution and partial density of states were compared for all the pseudopotentials with different relativistic treatments, providing insight into the orbital contributions of electrons to the density of levels. Our study provides a deeper understanding into the impact of electronic pseudopotentials and relativistic treatments on the electronic and structural properties of GaN.